FONOLOGI DAN MORFOLOGI BAHASA ARAB 'AMIYAH MESIR - Mufrodi, Mufrodi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
The use of Arabic language, it is divided into two, namely Arabic fuṣhâ and ‘âmiyah. Arabic fuṣhâ used as a written language, and Arabic ‘âmiyah used as a spoken language. In daily activities, Arab people used Arabic ‘âmiyah more frequently. This is due to a fairly high level of formality that is owned by Arabic fuṣhâ, that should be in the spoken language is communicative, consultative, relaxed and intimate, both in term of morphological and syntactical. In the Egyptian Arabic occur in phonological and morphological differences were deemed difficult for students who only learn Arabic fuṣhâ. The difficulty that arises due to the ignorance of students to the differences that occur between Arabic fuṣhâ and Egyptian dialect. With an understanding of phonological and morphological of Arabic ‘âmiyah expected that the students of Arabic language or people who have learned fuṣhâ can understand-at least a few understanding-spoken language so that communication will run smoothly.DOI: 10.15408/a.v2i2.2184